Perbandingan Makna Majaz dalam Surah Al-Baqarah antara Terjemah Al-Qur’an Kementerian Agama dan H.B. Jassin (Studi Analisis Kritik) - Faisal Mubarak; Arifin, Ahmad; Abdul Latif; Ade Destri Deviana; Syamsuni; M. Kamil Ramma Oensyar (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
Majaz is a pronunciation used not in its original meaning because there is a relationship ('alaqah) and a sign (qarinah) that diverts one's understanding to arrive at the original meaning. In the Qur'an there are majaz expressions that are not in their original meanings, it is necessary to look at the context of the sentences in the verse and refer to the books of interpretation and balaghah to find their original meanings. The purpose of this research is to know the differences in the translation of H.B. Jassin and the Ministry of Religion against the specified majaz of ayat. The type of research used in this study is library research. Primary data from verses containing majaz in Surah Al-Baqarah translation H.B. Jassin and the Ministry of Religion. The researcher uses content analysis for data analysis model. The results emergence there are 14 figurative expressions in Surah Al-Baqarah have different translations between H.B. Jassin's translation and the Ministry of Religious Affairs' translation. The differences be divided into two categories: differences in meaning, which include literal (harfiyyah) meaning and interpretive (tafsiriyah) meaning, and differences in the type of word meaning, which include differences in the type of noun (isim) and verb (fi'il).